MENINGKATKAN KREATIVITAS AUD MELALUI METODE PEMBELAJARAN LOOSE PART MELALUI KURIKULUM MERDEKA - Nurliyah Nasution; Yuli Rahma Sari; Nadilla Septria; Rika Juriyanti (Jurnal Al Athfaal, 2023)
This independent curriculum program encourages teachers to improve the learning creativity of children of this age through loose part media. This research also aims to gain insight into how the use of Loose Parts media can improve the development of early childhood creativity at RA ASY-SYI''AR, Bandar Masilam District. This research was conducted through direct observation of learning activities in the classroom, observation data sources in the form of interviews with class teachers and parents of RA ASY-SYI''AR students. Based on the percentage results from several sources, the researcher concluded that the loose part game is a learning media that uses used materials in increasing creativity in early childhood, the use of loose part learning media can facilitate children in expressing their creativity through their imaginative and creative ideas. The loose parts method used at RA ASY-SYI''AR can increase creativity in children because it can give children the freedom to explore directly and can stimulate children's curiosity about something new.